Phonological Training and Word Learning in a Novel Language - Li, Yixun; Wang, Min; Li, Chuchu; Li, Man (Frontiers in Communication, 2022)
In reading Chinese words, learners may process segment and tone either separately or as an integral unit, as evidenced in previous research. The present study compared two ways—Segmental versus Whole-Syllable-Based Training— for improving learners’ phonological and word learning in Chinese as a novel language, while controlling for learners’ musical ability, an important factor that may contribute to phonological learning. Forty-two American college students learned Chinese words represented by Pinyin, a romanized script which denotes the pronunciation of Chinese characters. Before the training, all participants were introduced to the phonology and Pinyin system. Then, they were trained on the pronunciation and meaning of the Pinyin words with or without an emphasis on separating the tonal from segmental information. All participants’ musical ability was assessed using a musical ability test. Learning outcomes were measured through tasks of same-different phonological judgment, tone identification, and word comprehension. Results showed the equal success of the two training methods, probably due to the consistent involvement of Pinyin and learner’s reliance on segment and tone as an integral unit rather than separate cues in phonological and word learning. Furthermore, musical ability seems to play a role in phonological and word learning among novel learners of Chinese.